Manipulasi Laporan Keuangan dalam Perspektif Etika dan Tanggung Jawab Sosial Perusahaan: Tinjuan Sistematis Literatur - Muhammad Farsya Firdaus; Rani Anggeraeni; Neli Junira; Muhammad Fariz Azkia (Journal of Economic and Business Advancement, 2026)
This study aims to analyze the conceptual relationship between financial statement manipulation, business ethics, and corporate social responsibility through a Systematic Literature Review approach. This study is motivated by increasing demands for corporate transparency and accountability amid global economic dynamics that place financial reporting integrity as the basis for organizational legitimacy. The research is non-empirical, analyzing twelve scientific articles systematically selected from academic databases based on thematic relevance and study quality. The analysis was conducted using descriptive-qualitative synthesis through thematic categorization and cross-study comparison to identify patterns of relationships between variables. The results of the study indicate that financial statement manipulation is related to weak internalization of organizational ethics and market legitimacy pressures. Business ethics acts as a normative mechanism that strengthens reporting integrity, while corporate social responsibility functions as a reputational control that can suppress or cover up opportunistic management practices